PENERAPAN MODEL PEMBELAJARAN PROBLEM BASED LEARNING BERBANTUAN MEDIA VIDIO ANIMASI DILENGKAPI QUIZ WORDWALL UNTUK MENINGKATKAN HASIL BELAJAR SISWA DI SMA MUHAMMADIYAH WAINGAPU - Arifudin; Tamu Ina, Anita; Louise Makatita, Audey (Jurnal Biogenerasi, 2024)
This study aims to explore the impact of implementing Problem Based Learning (PBL) using animated video media and Wordwall quizzes on student learning outcomes at SMA Muhammadiyah Waingapu. The research was conducted using the Classroom Action Research (CAR) method with Grade X Social Sciences students in the academic year 2023/2024. affective aspects. Therefore, it can be concluded that implementing PBL with animated video media and Wordwall quizzes effectively enhances student learning outcomes and achieves the expected level of mastery in science subjects at SMA Muhammadiyah Waingapu.